Elemen Anti Hadis Dalam Ucapan Kepada Konferensi Politik Nasional Oleh Kassim Ahmad: Satu Penilaian - Wan Mohd Fazrul Azdi Wan Razali; Mohd Rumaizuddin Ghazali; Mohd Azhar Ibrahim Residi; Fikri Muharam (Universiti Sains Islam Malaysia, 2024)
Abqari Vol. 6, 2015